A new genus and species of Schizogyniidae (Acari: Mesostigmata) associated with carabid beetles (Coleoptera: Carabidae) from Ukraine - Trach, Viacheslav A.; Seeman, Owen D. (Zootaxa, 2014)
A new genus and species of Schizogyniidae (Acari: Mesostigmata: Celaenopsoidea), Euroschizogynium calvum gen. nov. and sp. nov., associated with Scarites terricola Bonelli, 1813 (Coleoptera: Carabidae) is described from Ukraine, representing the first record of the family from the Palaearctic. Fusura civica Valle & Fox, 1966 is moved out of the Schizogyniidae and placed into the Megacelaenopsidae. A new diagnosis for the family Schizogyniidae and a key to genera are provided.